Desempenho motor de pacientes com acidente vascular cerebral em um jogo baseado em realidade virtual - Fernandes, Aline Braga Galvão Silveira (2011)
The Cerebral Vascular Accident (CVA) is the leading cause of motor disability in adults and elderly and that is why it still needs effective interventions that contribute to motor recovery. Objective: This study was aimed to evaluate the performance of stroke patients in chronic stage using a virtual reality game. Method: 20 patients (10 with injury to the left and 10 to the right side), right-handed, average age 50.6 ± 9.2 years, and 20 healthy subjects with average age of 50.9 ± 8.8, also right-handed participated. The patients had a motor (Fugl-Meyer) and muscle tone assessment (Ashworth). All participants made a kinematic evaluation of the drinking water activity and then underwent training with the table tennis game on XBOX 360 Kinect®, 2 sets of 10 attempts for 45 seconds, 15 minutes rest between sets, giving a total of 30 minutes session. After training the subjects underwent another kinematic evaluation. The patients trained with the right and left hemiparect upper limb and the healthy ones with the right and left upper limb. Data were analyzed by ANOVA, t Student test and Pearson correlation. Results: There was significant difference in the number of hits between the patients and healthy groups, in which patients had a lower performance in all the attempts (p = 0.008), this performance was related to a higher level of spasticity (r = - 0.44, p = 0.04) and greater motor impairment (r = 0.59, p = 0.001). After training, patients with left hemiparesis had improved shoulder and elbow angles during the activity of drinking water, approaching the pattern of motion of the left arm of healthy subjects (p < 0.05), especially when returning the glass to the table, and patients with right hemiparesis did not obtain improved pattern of movement (p > 0.05). Conclusion: The stroke patients improved their performance over the game attempts, however, only patients with left hemiparesis were able to increase the angle of the shoulder and elbow during the functional activity execution, better responding to virtual reality game, which should be taken into consideration in motor rehabilitation